Kontaminasi Salmonella sp. pada Telur Ayam: Studi Komparatif Antara Peternakan dan Pasar Tradisional - Suswati, Enny; Anggraini, Nanda Dewi; Sudarmanto, Yohanes (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2025)
Eggs are a food ingredient consumed daily by the community; eggs infected with Salmonella sp. can cause various health problems. The global prevalence rate of salmonellosis disease based on data from the Institute for Health Metrics and Evaluation in 2019 stated that it was 4.22 per 100,000 population with a mortality rate due to salmonellosis of 1.72%. The end of this study was to see the comparison of Salmonella sp. contamination in chicken eggs in terms of differences in location on farms and in the Sukowono market. This study included 70 randomly selected chicken eggs from two different locations, namely chicken farms and traditional markets in Sukowono sub-district, using the egg shell swab method, and then bacterial culture was carried out using SSA (Salmonella Shigella Agar). The prevalence of Salmonella sp. contamination in the chicken eggs examined was 25.7%. There was a significant difference in the comparison of Salmonella sp. contamination in chicken eggs in terms of differences in location on farms and market traders. Eggs from farms have lower Salmonella sp. contamination compared to eggs from traditional markets.